First Molecular Evidence of Tomato chlorotic spot virus Infecting Tomatoes in Cuba - Martínez Zubiaur, Yamila (2016)
UCR::Vicerrectoría de Investigación::Unidades de Investigación::Ciencias Básicas::Centro de Investigación en Biología Celular y Molecular (CIBCM)